(untitled) (Indonesian Tourism Justice Review, 2025)
The rapid expansion of tourism in Bali has placed significant pressure on the island’s indigenous communities, particularly in terms of land rights and local ownership. This paper examines the intersection of tourism development and land justice in Bali, focusing on the challenges faced by indigenous communities in preserving their ancestral lands amid growing commercial interests. Using a legal and social justice framework, the paper investigates how tourism-related land acquisitions, government policies, and corporate land use impact the traditional land tenure systems of Bali’s indigenous peoples. Through a combination of interviews with local community leaders, legal experts, and case studies, the paper highlights the social, cultural, and economic implications of land dispossession, displacement, and the erosion of indigenous rights. The study argues for a rethinking of land development policies that prioritize indigenous land rights and proposes strategies for integrating community-based land management practices into tourism development planning. In conclusion, the paper calls for stronger legal protections and a more equitable approach to tourism that respects the rights of indigenous populations.